1992
DOI: 10.1161/01.cir.85.3.1197
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights into coronary collateral circulation.

Abstract: T he coronary collateral circulation is an alternative source of blood supply to the myocardium jeopardized by failure of the original vessel to provide adequate flow to the major epicardial branches of the coronary artery. There has been considerable debate, however, concerning the functional role of collaterals in humans.1-9 Extensive studies carried out in the past several years in experimental animals, in autopsy materials, or in intact human hearts have confirmed the substantial potential of collaterals i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(81 citation statements)
references
References 89 publications
2
78
0
1
Order By: Relevance
“…1 Collateral circulation potentially offers an important alternative source of blood supply when the original vessel fails to provide sufficient blood. 2 Timely enlargement of collaterals may even avoid transmural myocardial infarction (MI) and death in symptomatic patients. 3 As early as in 1956, Baroldi et al 4 demonstrated the presence at birth of mostly corkscrew-shaped collaterals in normal human hearts, with a lumen diameter of 20 to 350 m and lengths ranging from 1 or 2 cm to 4 or 5 cm.…”
Section: Coronary Collateral Circulation: Current Knowledgementioning
confidence: 99%
“…1 Collateral circulation potentially offers an important alternative source of blood supply when the original vessel fails to provide sufficient blood. 2 Timely enlargement of collaterals may even avoid transmural myocardial infarction (MI) and death in symptomatic patients. 3 As early as in 1956, Baroldi et al 4 demonstrated the presence at birth of mostly corkscrew-shaped collaterals in normal human hearts, with a lumen diameter of 20 to 350 m and lengths ranging from 1 or 2 cm to 4 or 5 cm.…”
Section: Coronary Collateral Circulation: Current Knowledgementioning
confidence: 99%
“…The growth of blood vessels is a well-documented physiological response to myocardial infarction (3)(4)(5). The mechanism(s) that regulates the response of cardiac tissue to ischemia and the role of a chemical mediator in the angiogenic process have not been established, although several investigations demonstrated the presence and release of an endothelial cell growth…”
Section: (R)-hete 12(s)-hetementioning
confidence: 99%
“…[1][2][3] However, even well-developed collaterals may not fully substitute normal coronary flow, and surgical or percutaneous revascularization is often indicated. The incidence of acute myocardial infarction (MI) after recanalization of a chronic total coronary occlusion (CTO) 4,5 suggests that collaterals that are no longer required to uphold myocardial perfusion may regress after revascularization.…”
mentioning
confidence: 99%